Variation in Glucose-6-Phosphate Dehydrogenase Activity in the Adults and Different Immature Stages of Aedes aegypti - SundarMohanty, Suman; Singh, Karam Vir; Kanojia, Phool Chand; Bansal, Shiv Kumr (Asian Journal of Biological and Life Sciences, 2015)
In India, Aedes aegypti is the principal vector of the dengue viruses. Dengue viruses require a stipulated time to replicate and disseminate inside the mosquito’s body before transmission to naı¨ve hosts can occur. Glucose-6-phospahte dehydrogenase (g6pd) is a NADP generating enzyme and support many biosynthetic reactions in Ae. aegypti. The study was aimed to record the variation in g6pd activity with increasing age and to monitor the impact of environmental conditions on the g6pd activity. The g6pd activity in newly emerged Ae. aegypti adults was higher than larvae, pupae and elder mosquitoes. The activity of the g6pd was decreased with increasing age of adults and was consistent for all the cases upto 20 days. There was a significant higher g6pd activity recorded in the field collected larvae, pupae and females than the laboratory reared mosquitoes. The enhanced g6pd activity in field collected mosquitoes may be due to higher rate of metabolism and this leads to more risk of disease transmission. Therefore, larval control strategies will be more effective for the control of the vector borne disease in the desert region. The g6pd activity may be used as a tool for the prediction of age of adults for a particular period.
Keywords: Age; dengue; longevity; mosquito; vector